Development and Preliminary Evaluation of the Betang Transparent Card for Teaching Fraction Addition with Unlike Denominators in Elementary School - Franatha, Edy; Putra, Chandra Anugrah; Misyanto, Misyanto (Lembaga Penelitian dan Pemberdayaan Masyarakat, 2026)
This study aimed to develop the Betang Transparent Card learning medium for teaching the addition of fractions with unlike denominators to fifth-grade elementary school students and to examine its feasibility, practicality, and preliminary effectiveness. The study employed a Research and Development approach using the ADDIE model, which comprises analysis, design, development, implementation, and evaluation. The research was conducted at SD Negeri 2 Karang Tunggal during the 2025/2026 academic year. The participants included six students in the limited trial and 18 students in the effectiveness assessment. Product validation involved a subject matter expert, a media expert, and a language expert. Data were collected using expert validation sheets, a student response questionnaire, classroom observations, and pretest and posttest assessments. The results showed feasibility scores of 93.33% from the subject matter expert, 96.47% from the media expert, and 100% from the language expert, all of which were classified as highly feasible. The student response score reached 90%, indicating a high level of practicality. The mean achievement score increased from 66.7 on the pretest to 87.8 on the posttest, with an N-gain score of 0.63 in the moderate category. These findings provide preliminary evidence that the Betang Transparent Card medium is feasible, practical, and potentially useful for supporting students’ understanding of equivalent fractions and the addition of fractions with unlike denominators. Further studies involving larger samples and comparison groups are required to establish its effectiveness more conclusively.